Surviving and Thriving: The Role of Social Support in Mitigating Culture Shock Among East Nusa Tenggara Students in Salatiga - Situmeang, Louis Van Gall; Rahayu, Maria Nugraheni Mardi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
This study aims to examine the relationship between social support and culture shock among sojourner students from East Nusa Tenggara (NTT) studying at Satya Wacana Christian University, Salatiga. The research is motivated by the phenomenon of many students from NTT migrating to Java Island to obtain quality education but often facing cultural adaptation challenges. The study employed a quantitative approach with a correlational design. The variables examined were social support based on Zimet et al.'s (1988) concept, which includes aspects of family support, friends, and significant others, and culture shock based on Taft's (1977) concept, which encompasses aspects of tension, feelings of loss, rejection of new cultures, role confusion, surprise and anxiety, feelings of helplessness, and interpersonal stress. The research sample consisted of 80 students from NTT, selected through accidental sampling technique. Data collection utilized questionnaires with Likert scales. Data analysis was performed using Pearson product-moment correlation through SPSS. The results showed no significant relationship between social support and culture shock, with a correlation coefficient of r= -0.010 and significance value of 0.467 (p>0.05). 65% of respondents had moderate levels of social support, 21.3% low levels, and 13.8% high levels. As for culture shock, 61.3% of respondents were in the moderate category, 13.8% in the low category, and 25% in the high category. These findings indicate that while social support is important for emotional comfort, the intensity of culture shock experienced by students is more influenced by the complexity of differences in values, language, and cultural norms. Sojourner students who first arrive in Java typically face culture shock due to significant differences in lifestyle, language, social norms, habits, and cultural values that require time to adapt to.